RELATIONSHIP AND DIFFERENCES BETWEEN SCIENCE, PHILOSOPHY, RELIGION - Rizqi Ubaidil Arifin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The study of the relationships and differences between science, philosophy, and religion is an attempt to understand the epistemological foundations that shape human civilization. Science relies on rationality and empirical observation in seeking objective truth, while philosophy serves as a critical reflection on the nature of knowledge, existence, and life values. Meanwhile, religion provides a transcendental dimension through revelation as a source of absolute truth that cannot be fully grasped by human reason. The relationship between the three is complementary; science explains natural and social phenomena, philosophy provides a rational and methodological basis, and religion guides the moral and spiritual direction of human life. However, differences arise in the sources of truth and the methods of attaining itscience relies on empiricism, philosophy on reason, and religion on revelation. This study concludes that the integration of the three can produce a complete and balanced worldview between the rational, ethical, and spiritual dimensions of humankind.